Anxiety predicts impulsive-compulsive behaviours in Parkinson's disease: Clinical relevance and theoretical implications. (April 2022) - Di Rosa, Elisa; Mapelli, Daniela; Ronconi, Lucia; Macchia, Eleonora; Gentili, Claudio; Bisiacchi, Patrizia; Edelstyn, Nicky
Abstract: Patients with Parkinson's disease (PD) often present symptoms of anxiety, depression and apathy. These negative affect manifestations have been recently associated with the presence of impulsive compulsive behaviours (ICBs). However, their relation with the use of dopamine replacement therapy (DRT), a renewed risk factor for ICBs, is still not fully understood. Elucidating the role of these different ICBs predictors in PD could inform both prevention/intervention recommendations as well as theoretical models. In the present study, we have analysed data collected in 417 PD patients, 50 patients with Parkinsonian symptoms but with scan without evidence of dopaminergic deficit (SWEDD), and 185 healthy controls (HC). We examined each patient's clinical profile over a two-year time window, investigating the role of both negative affect and DRT on ICBs. Results confirmed the presence of higher levels of anxiety in both the clinical groups, and of higher level of ICBs in SWEDD patients, respect to both PD and HC. Mixed model analyses revealed a statistically significant association between anxiety and ICBs in the SWEDD patients who did not take any DRT. Findings suggest the independence between anxiety and DRT in ICBs development, and provide new evidence for the motivational opponency theoretical framework. Highlights: Patients with Parkinson's disease show higher level of anxiety symptoms when compared with healthy controls. Anxiety (STAI-Y total score) significantly predicts impulsive-compulsive behavior in patients without dopaminergic deficits. Anxiety management may represent a prevention strategy for impulsive-compulsive behavior in Parkinson's disease.